GP.02 Resting state functional connectivity: a biomarker for pre-operative cognitive function and cognitive outcome following surgery in patients with diffuse glioma. (June 2017) - Lang, S; Gaxiola-Valdez, I; Partlo, L; Goodyear, B; Kelly, J; Federico, P
Abstract : Background: Resting state functional connectivity (RSFC) in the fronto-parietal network (FPN) has been associated with cognitive ability. For this reason, it was hypothesized that RSFC connectivity of the FPN would be related to cognition in patients with diffuse glioma. To assess this relationship, pre-operative cognitive status was correlated to patient specific connectivity within the FPN. Further, we assessed whether RSFC could predict neuropsychological outcome following surgeryMethods: Sixteen patients with diffuse glioma underwent neuropsychological assessment and pre-operative task and resting state fMRI. Thirteen had post-operative cognitive assessment at one-month post-surgery. RSFC in a subject-specific FPN was correlated with pre- and post-operative cognitive scores.Results: Higher connectivity within the FPN was associated with lower composite cognitive scores, while higher connectivity of the parietal node of the tumor-affected hemisphere was associated with lower fluid cognition but not crystallized cognition. Higher connectivity values between the parietal node of the healthy hemisphere and the rest of the FPN was associated with better neuropsychological outcome one month after surgery.Conclusions: RSFC between key nodes of the FPN is associated with cognitive performance in patients with diffuse glioma and is a promising biomarker for cognitive outcome following surgery.